2022
DOI: 10.21203/rs.3.rs-1091162/v2
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Resilience among undergraduate nursing students: Findings of the first cross-sectional study in Palestine

Abstract: Background Resilience has emerged as a concept that could explain and predict good academic and well-being of students in stressful and traumatic situations. This study was conducted to assess resilience and identify predictors of high resilience scores among nursing students in Palestine. Methods This cross-sectional study adhered to the Strengthening the Reporting of Observational Studies in Epidemiology statement. Undergraduate nursing students in all academic years were recruited and asked to complete a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…There was no significant association found between the assigned ward and age variables and the levels of felt stress and moral resilience. The nurses were observed to exhibit a moderate level of resilience, while it is in contrast to Alkaissi et al (2022) [25] study, who reported from total of 290 participants responded to the survey, providing data on trait, state, and combination resilience scores.…”
Section: Discussionmentioning
confidence: 62%
“…There was no significant association found between the assigned ward and age variables and the levels of felt stress and moral resilience. The nurses were observed to exhibit a moderate level of resilience, while it is in contrast to Alkaissi et al (2022) [25] study, who reported from total of 290 participants responded to the survey, providing data on trait, state, and combination resilience scores.…”
Section: Discussionmentioning
confidence: 62%
“…Additionally, resilience entails learning and growing stronger from accumulating experiences. Resilience has emerged as a concept that could explain and predict good academic and well-being of students in stressful and traumatic Basma A., et al situations (Alkaissi et al, 2022). Also, the impact of nursing students' personal resilience on issues such as attrition, managing stress in the clinical environment and developing coping skills to overcome adversity has resulted in increased interest in this area (Rice & Liu, 2016).…”
Section: Introductionmentioning
confidence: 99%